Compactness Ratio as an Indicator for the Efficiency of Road Transportation Network in Postmodern Iraqi Cities - Mohammed Abid, N (KnE Engineering, 2018)
The location of the city affects the composition and distribution of land uses, where topography and terrain works to influence the forms taken by cities and regions and the modes of transport used. Thus, the proportion of solidarity greatly affect the roads and streets, which take multiple forms vary depending on the modes of transport used in them. Since the distribution of road networks is efficient and achieves the mobility of the population in the city the more efficient the activities and events distributed in the area of the city, so it was necessary to rely on two main factors, the area and the population in measuring the degree of availability of the road network in the city to evaluate the efficiency of Connected. As the greater the proportion of the compactness of the city, the more concentrated uses of the ground at a higher density and less transport distance, which is the city of Iraq pre-modernity to give greater efficiency of the transport network and vice versa when the proportion of solidarity to the city scattered uses of the earth less intensity and a greater transport distance, Post-modernity to give less efficiency to the transport network. Therefore, it was necessary to assess the efficiency of the network in the urban area by measuring the proportion of solidarity. Therefore, the index of the ratio of the integration of the transport network as an indicator of the integration of the city through its application to the urban centers of the provinces of Iraq to measure the efficiency of the transport network.